Pengaruh Pembiayaan Mudharabah dan Murabahah terhadap Pertumbuhan UMKM Studi Kasus pada Anggota di BMT di Kecamatan Percut Sei Tuan - Mutthaqin, M. Satrya; Hasibuan, Faisal Umardani; Cahyadi, Rahmad; Muda, Iskandar; Soemitra, Andri; Yusrizal, Yusrizal (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of mudharabah and murabahah financing on the development of Micro, Small, and Medium Enterprises (MSMEs) among Baitul Maal wat Tamwil (BMT) members in Percut Sei Tuan District. The research background is based on the strategic role of MSMEs in the national economy, but they still face a major obstacle in the form of limited capital. BMT as a sharia financial institution is present to offer financing solutions based on sharia contracts, specifically mudharabah and murabahah, which are expected to be able to support the growth of community businesses. The research method used a quantitative approach with primary data collected through questionnaires. The research subjects were BMT members in Percut Sei Tuan District, with a Likert scale as the measurement instrument. Data analysis was conducted through classical assumption tests (normality, multicollinearity, and heteroscedasticity tests) and multiple regression tests including the t-test, F-test, and coefficient of determination (R²). The results showed that mudharabah financing had a positive and significant effect on the development of MSMEs, while murabahah financing had no significant effect. Simultaneously, both types of financing influence the development of MSMEs with an Adjusted R Square value of 0.165, meaning that only 16.5% of the variation in MSME development can be explained by these two variables, while the remaining 83.5% is influenced by other factors outside the study. This finding emphasizes the importance of optimizing mudharabah financing in encouraging MSME growth. Furthermore, additional strategies are needed, both from Islamic financial institutions and local governments, to improve access to capital and Islamic financial literacy for MSMEs.